Associations of childhood trauma with food addiction and insulin resistance in African-American women with diabetes mellitus. (1st October 2019) - Stojek, Monika M.; Maples-Keller, Jessica L.; Dixon, Hayley Drew; Umpierrez, Guillermo E.; Gillespie, Charles F.; Michopoulos, Vasiliki
Abstract: Food addiction (FA) describes a group of disordered eating behaviors. Childhood trauma has been associated with adult FA and trauma has known effects on the endocrine system, but it is unclear whether FA is associated with insulin resistance. We hypothesized that severity of childhood trauma will be associated with FA and higher insulin resistance (HOMA-IR) in a sample of obese women with type 2 diabetes mellitus (T2DM), and that FA will mediate the association between childhood trauma and HOMA-IR. Women with a diagnosis of T2DM ( N  = 73; M BMI  = 35.86, SD BMI  = 7.72; M age  = 50.59, SD age  = 9.72) were recruited from a diabetes clinic at a county hospital. Participants completed the Childhood Trauma Questionnaire and the Yale Food Addiction Scale. Fasting blood samples were obtained from 64 participants to assess plasma hemoglobin A1c (HbA1c), insulin and glucose (used to calculate HOMA-IR); Oral Glucose Tolerance Test (OGTT) was performed to measure change in glucose and insulin secretion. 48% of the sample met diagnostic criteria for FA. Women with FA reported significantly higher HOMA-IR ( F  = 25.692, p  < 0.001, df  = 1, 62), HbA1c ( F  = 4.358, p  = 0.041, df  = 1, 62), and OGGT glucose ( F  = 5.539, p  = 0.022, df  = 1, 62) as well as severity of childhood trauma ( F  = 10.453, p  = 0.002, df  = 1, 71). In a hierarchical linear regression controlling for BMI, income level, and T2DM treatment, the severity of childhood trauma did not contribute to the prediction of HOMA-IR ( β  = −0.011, p  = 0.942) whereas FA did ( β  = 0.422, p  = 0.007). In a bootstrapped mediation analysis, the association between childhood trauma and HOMA-IR was mediated by FA severity ( b  = 0.596, p  = 0.020). Understanding the psychological factors that contribute to HOMA-IR in an underserved population of African American women may lead to more effective diabetes management and prevention strategies.